Student's Perception towards ICT Use in Government and Non- Government Schools of Surkhet District - Acharya, Gobinda Prasad (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
This article delves into students' perceptions of Information and Communication Technology (ICT) use in government and non-government schools in Surkhet District. The main objective of the article is to explore the perception of students towards the use of ICT in government and non-government school in Surkhet district. In this article, a mixture of article methods is used including both quantitative and qualitative approaches. All the secondary level students in 18 schools of Surkhet district was the population of the article. Among the students of 18 schools, 424 were selected as sample. Questionnaires were used as the source for the data collection. The article used the statistical tools like Regression analysis to find out the perception of the students towards ICT use in schools. Data collected from both school types revealed demographic distributions and attitudes toward ICT. Government school respondents were primarily aged 12-13, while non-government schools had more respondents across all age groups. Males were the majority in both. The regression model analyzing students' perception of ICT use displayed a moderately strong positive correlation (R = 0.610), with 37.2 percent variance explained by factors like Access to Personal Device, Digital Literacy, Access to School IT Resources, and ICT Integration in Curriculum. Constructs showed good reliability and validity, affirming measurement accuracy. Results highlighted the positive impact of examined factors on ICT use, underlining the significance of resource access, digital literacy, and curriculum integration. Non-government schools had higher mean scores in computer and internet skills, possibly due to infrastructure or resource differences. Notable disparities existed between government and non-government schools in combined school and home ICT use and confidence levels, with gender differences also noted, warranting further exploration or intervention. The article underscores the need for improving access to resources, enhancing digital literacy, and integrating ICT in curricula to positively influence students' perceptions and use of ICT.